The lslamization of Central Java: the Role of Muslim Lineages in Kalioso - Headley, Stephen (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1997)
This article discusses trends and patterns of Islamization inland Javanese descent who performed a local Muslim family in Kalioso, Central Java, in the late 17th century. The question that should be asked is how the Java community process of Islamization in a smaller community level, district or rural? The pattern is used in the process of Islamization that took place at the level of the communities, especially in inland Java? Is it true that the spread of Islam in the villages also run politically, such as the establishment of the Sultanate of Demak, or take a more cultural way?DOI: 10.15408/sdi.v4i2.780